Determination of Haemaglutinin and Gene Encoding Fibronectin Binding Proteins Staphylococcus aureus Isolated from Dairy Milk Cows - Feny Prabawati Pratomo; Siti Isrina Oktavia Salasia; Syarifudin Tato (Universitas Gadjah Mada, 2011)
Staphylococcus aureus is a major pathogen causing clinical and subclinical mastitis in dairy milk cows. Themastitis has immense economical impacts, where it reduces of the quantity and quality of milk production.The aims of the research were to analyse haemaglutinin and gene encoding fbronectin binding proteins.Nineteen Staphylococcus aureus isolates used in the present study were isolated from dairy milk cows fromYogyakarta, Solo, Boyolali and Sumedang. The haemagluitinin of S. aureus were determined based onhaemaglutination reaction to erythrocytes of rabbit. Detection of gene encoding fbronectin binding proteinscould be performed with specifc primers using polymerase chain reaction (PCR). The results of studiesshowed that most of S. aureus (78,95%) expressed haemaglutinin based on their ability to aglutinate rabbiterythrocytes. Analysis of gene encoding fbronectin binding proteins of S. aureus revealed gene fnbA withsize of approximately 1300 bp for 57,89% isolates, gene fnbB with size of approximately 900 bp for 31,58%isolates and both of gene fnbA and fnbB could be detected for 31,58% isolates. The characters of S. aureusbased on haemaglutinin, gene fnbA and fnbB of the present study could be used as an information to controlof S. aureus infection in dairy herds.